ภาวะปัญหาทางการเงินและการดำเนินงานของบริษัทในประเทศไทย - ภวิกา ศศิวงศ์ภักดี (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
To analyze the indirect costs of financial distress in Thailand because there is no conclusion on how financial distress affects corporate performance by creating the benefits or generating the significant losses in value. This paper investigates the link between financial distress and corporate performance by testing whether firms with high leverage are more likely to experience performance losses in industry downturns than other firms. Firm performance is measured by sales growth, changes in operating income and stock returns relative to industry average. This study also tries to minimize the problem of reverse causality between the poor performance and financial distress. Besides, this thesis further investigates the relation between firm size and corporate performance and also examines how a firm s financial condition affects important corporate decisions during time of economic distress. The sample consists of 1,619 publicy traded firm-years in the 1990 to 1999. This study finds no obvious conclusion that financial distress are costly because the highly leverage firms have insignificant performance losses in industry downturn. A similar result takes place in firm size and the firm s response in period of economic distress. However, the result indicates that the highly leverage firms tend to experience lower operating income than their competitors even in a good time. Moreover, the firms that have high prior investment rate, as proxied by fix assets to total assets, have influenced on firm performance by increasing significant sales growth and changes in operating income.